Parameter Estimate for Spatial Lag Regression Model with Outlier - Harini, Sri; Sheppy, Siscaviyana; Siti Nurmala Sari, Marita; ., Purhadi (International Journal of Engineering and Technology, 2019)
Spatial lag regression is the result of linear regression model development that considers the effect of spatial data to the dependent variable, the Spatial Autoregressive Model. In the model of spatial lag regression model, it is often found there is an outlier that affects the created model. One of the methods to detect the outlier from the spatial regression model is by using the S estimator model. The S estimator method is a method that is used to determine the outlier by minimizing the objective function and the function of the number of error square. The result of the study shows the interpreting parameterÂ 14Ø®Â²m+1=XTØ¯â€°imX-1XTØ¯â€°imI-Ø¯Ù¾W1y"> Â Â that bears biased characteristic.Â Â